Czy "kataryzm" jest zjawiskiem należącym do przeszłości? Kilka obserwacji na temat przenikania się współczesności i historii - Dobkowski, Mariusz (Przegla̜d religioznawczy, 2016)
The author analyses how three cultural contexts: contemporary popular literature, regional Occitan identity and the newest historiography (i.e. its critical trend) shape the contemporary image of "Catharism." The scholar refers to "Catharism" in the area of today’s southern France only. In conclusion he states that each of the mentioned contexts uses the knowledge of "Catharism" in a different way: contemporary popular literature selects "Cathar" motifs, regional Occitan identity extends the definition of "Catharism" even to things not related to "Catharism," and contemporary historiography tries to negate "Catharism" as a real religious phenomenon.